Pertanggungjawaban Developer Atas Pembatalan Pembelian Rumah Oleh Calon Pembeli - Wibawa, Komang Satria; Figo, Muhammad Daffa; Astawa, I Nengah Dasi (Universitas Islam Sumatera Utara, 2024)
The purpose of this writing is to analyze the developer's responsibility for canceling home purchases by prospective buyers. This paper uses a normative type of writing. The approach used is an economic analysis approach to law that serves to overcome legal problems and assess the impact of the application of certain legal rules. Based on the analysis, it shows that the developer is domiciled as a seller and the prospective buyer has not been domiciled as a buyer because the sale and purchase transaction occurs when the parties have signed PPJB. Then, the developer's responsibility related to the cancellation of the purchase of a house by a prospective buyer before the existence of PPJB is to make a refund of the money paid by the prospective home buyer as regulated by Article 22H Paragraph (2) PP 12/2021 which is a form of the principle of absolute responsibility of the developer. The refund of the purchase of the house is preceded by an agreement on the amount of money that can be returned, where the prospective buyer can only get a maximum refund of 80% of the amount paid. Keyword: Developer; Prospective Buyer; Canceling Home Purchases